2020
DOI: 10.1016/j.compgeo.2020.103840
|View full text |Cite
|
Sign up to set email alerts
|

A new approach for longitudinal vibration of a large-diameter floating pipe pile in visco-elastic soil considering the three-dimensional wave effects

Abstract: A novel approach is presented to describe the dynamic interaction system of a large-diameter floating pipe pile and surrounding soils, taking the three-dimensional wave effects into account. The corresponding analytical solutions for longitudinal complex impedance are obtained and subsequently validated via comparisons with existing solutions. Comparative analyses are also performed to illustrate the difference between the present and previous solutions, concerning the wave propagation effect in the radial dir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
56
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 158 publications
(57 citation statements)
references
References 41 publications
0
56
0
1
Order By: Relevance
“…e test methods are as follows: firstly, the standard soil samples with different initial conditions are prepared by ring knife method; secondly, the soil samples are soaked in water (each sample has different amount of immersion); thirdly, the height change of soil samples after immersion is measured; finally, the soil samples are dried to calculate the moisture content change of each soil sample. [10] and Meng et al [12] showed that, under the condition of no load, the moisture absorption of the expansive soil gradually stabilized after 6 h and after 24 hours, and expansion was no longer changed). (4) e soil sample was put into the drying box for moisture content determination; (5) After 24 hours, the dried soil samples were taken out, and the weight of each soil sample was measured.…”
Section: Test Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…e test methods are as follows: firstly, the standard soil samples with different initial conditions are prepared by ring knife method; secondly, the soil samples are soaked in water (each sample has different amount of immersion); thirdly, the height change of soil samples after immersion is measured; finally, the soil samples are dried to calculate the moisture content change of each soil sample. [10] and Meng et al [12] showed that, under the condition of no load, the moisture absorption of the expansive soil gradually stabilized after 6 h and after 24 hours, and expansion was no longer changed). (4) e soil sample was put into the drying box for moisture content determination; (5) After 24 hours, the dried soil samples were taken out, and the weight of each soil sample was measured.…”
Section: Test Methodsmentioning
confidence: 99%
“…Moreover, several studies investigate the effects of temperature on the behavior of collapse loess [10,11]. When expansive soils are subjected to water changes, excessive deformation may be induced, which may threaten underground structures [12][13][14][15][16][17]. Since expansion and shrinkage are induced in expansive soils when subjected to water changes, more and more studies have been conducted to the deformation characteristic of reinforced expansive soil [18].…”
Section: Introductionmentioning
confidence: 99%
“…The biochemical characteristic parameters of the proposed coupled model are calibrated according to the relationship between the C/L values and the filling ages of borehole samples, the parameters are shown in Table 2. The mechanical characteristic parameters of MSW are selected based on the recommended parameter value range of typical landfills with high kitchen waste content in China [29][30][31]. A numerical model of landfill cell with a height of 40 m is established to predict the stabilization process of the Jiangcungou landfill.…”
Section: Prediction Of the Stabilization Process Of The Jiangcungou Landfill In Xi'an Chinamentioning
confidence: 99%
“…With the annually increased consumption of OPC, there is a strong need for sustainable development [26][27][28]. To improve the performance of cement-based materials and reduce CO2 emissions, special types of cement were applied as an alternative to OPC in certain situations, in which calcium sulfoaluminate (CSA) cement has attracted attention [29][30][31][32]. CSA has characters of rapid hardening, high early strength, resistance to sulfate attack, and tailored expansion [33].…”
Section: Introductionmentioning
confidence: 99%